TOWARD A CONCEPTUAL UNDERSTANDING OF SUFFERING IN NURSING CARE - Ayed Bedah Mohammed Alotaibi, Abdullah Nasser Mohammed Alnasser, Amani Mabkhoot Mohammed Alsaiari, Hayyan Abdulaziz Almansour, Bandar Zaben Alharbi, Najla Alhumaidi Obaid Almutairi, Norah Faihan Ayad Alotaibi, ,; Latifah Faihan Alotaibi, Maha Faihan Alotaibi, Hissah Faihan Alotaibi, Zahi Foriaan Alanazi, Eshraq Awad Al Johany, Naifah Enad Al-enezi, Rana Mutlaq Alotaibi, (Chelonian Research Foundation, 2022)
An intellectual basis for human suffering in research and nursing care A conceptual framework for human suffering in nursing care and research Health care and nursing both deal with suffering, which is an important yet elusive phenomenon. There is a dearth of significant literature on suffering, despite its significance and prevalence. Undoubtedly, a portion of the challenge in broadening this body of knowledge stems from the absence of a strong conceptual underpinning for investigating this phenomenon. While efforts have been made to bring about the necessary conceptual clarity, they have usually not been grounded in systematic study. The concept analysis approach was employed in this work to define the notion of suffering inductively and to make numerous contextual features of the concept clear. An incident or a perceived threat is given an extremely negative connotation in suffering, which is characterized as a unique, subjective, and multifaceted experience. There are provided implications of these findings for nursing practice and research, along with other contextual features of the notion. These findings contribute to the conceptual underpinning required to improve awareness and comprehension of the suffering that humans endure. Keywords: Suffering, Nursing care, Concept analysis, Negative meaning, Individualized, Subjective.